The current use of ultrasound to measure skeletal muscle and its ability to predict clinical outcomes: a systematic review. Issue 5 (19th July 2022) - Casey, Patrick; Alasmar, Mohamed; McLaughlin, John; Ang, Yeng; McPhee, Jamie; Heire, Priam; Sultan, Javed
Abstract: Quantification and monitoring of lean body mass is an important component of nutrition assessment to determine nutrition status and muscle loss. The negative impact of reduced muscle mass and muscle function is increasingly evident across acute and chronic disease states but is particularly pronounced in patients with cancer. Ultrasound is emerging as a promising tool to directly measure skeletal muscle mass and quality. Unlike other ionizing imaging techniques, ultrasound can be used repeatedly at the bedside and may compliment nutritional risk assessment. This review aims to describe the current use of skeletal muscle ultrasound (SMUS) to measure muscle mass and quality in patients with acute and chronic clinical conditions and its ability to predict functional capacity, severity of malnutrition, hospital admission, and survival. Databases were searched from their inception to August 2021 for full‐text articles in English. Relevant articles were included if SMUS was investigated in acute or chronic clinical contexts and correlated with a defined clinical outcome measure. Data were synthesized for narrative review due to heterogeneity between studies. This review analysed 37 studies (3100 patients), which met the inclusion criteria. Most studies ( n = 22) were conducted in critical care. The clinical outcomes investigated included functional status at discharge (intensive care unit‐acquired weakness), nutritional status, and length of stay. SMUS was also utilized in chronic conditions such as chronic obstructive pulmonary disease, chronic heart failure, and chronic renal failure to predict hospital readmission and disease severity. Only two studies investigated the use of SMUS in patients with cancer. Of the 37 studies, 28 (76%) found that SMUS (cross‐sectional area, muscle thickness, and echointensity) showed significant associations with functional capacity, length of stay, readmission, and survival. There was significant heterogeneity in terms of ultrasound technique and outcome measurement across the included studies. This review highlights that SMUS continues to gain momentum as a potential tool for skeletal muscle assessment and predicting clinically important outcomes. Further work is required to standardize the technique in nutritionally vulnerable patients, such as those with cancer, before SMUS can be widely adopted as a bedside prognostic tool.